Advancing Knowledge with Ultraviolet- Spectroscopy: Recent Trends and Future Insights - Dandekar, Mayur R. (Asian Journal of Pharmaceutics (AJP), 2024)
One popular analytical method for looking at molecules’ electronic transitions is UV-Vis spectroscopy. The theoretical foundations of UV-Vis spectroscopy, including the theory of molecular orbits and the kinds of electronic transitions that cause absorption in the UV and visible spectrums, are examined in this review article. It also discusses the variables that affect absorption spectra, including conjugation, chromophores, and solvent effects. Important uses such as statistical analysis, molecular structure identification, and conjugated system research are also highlighted in the text. It is explored what the future holds for UV-Vis spectroscopy in both industry and research.